THE ROLE OF ECULUZIMAB IN THE PROGNOSIS OF SHIGA TOXIN- ASSOCIATED HEMOLYTIC-UREMIC SYNDROME IN CHILDREN: A LITERATURE REVIEW - Ramos, Gustavo Almeida; Mello, Amanda Moreira de Araújo; Pinheiro, Camila Fontes; Reis, Cíntia Pereira; Moreira, Stephania de Oliveira Laudares; Carneiro, Lílian Carla; Pinto, Murillo de Sousa (Anais Eventos, 2025)
Hemolytic-Uremic Syndrome (HUS) is a rare and severe thrombotic microangiopathy characterized by hemolytic anemia, thrombocytopenia, and acute kidney injury, predominantly affecting children. The form associated with Shiga toxin- producing Escherichia coli (STEC-HUS) is the most prevalent in this age group, with high morbidity and a significant risk of renal sequelae and the need for renal replacement therapy, as evidenced by national studies. Eculizumab, a complement C5 inhibitor, has revolutionized the prognosis of Atypical Hemolytic-Uremic Syndrome (aHUS), but its role in pediatric STEC-HUS remains controversial. This article, through an integrative literature review in the PubMed and SciELO databases, analyzed the influence of eculizumab on the clinical outcomes of STEC-HUS in children, aiming to support the discussion on its potential inclusion in the Brazilian healthcare system. The results indicate that while there is evidence of long-term benefit in renal protection, the efficacy of eculizumab in the acute phase and on neurological outcomes is not consistently demonstrated. Studies are often limited by indication bias and small sample sizes. Given the high cost and scientific uncertainties, it is concluded that eculizumab should not be a universal first-line therapy for STEC-HUS. Its use must be highly individualized, reserved for severe or refractory cases with confirmed complement activation, rigorous clinical protocols, and genetic testing. There is a pressing need for randomized, multicenter clinical trials to define the subgroup of pediatric patients with STEC-HUS who would truly benefit from this therapy, paving the way for more solid evidence-based health policies in Brazil.